Neodymium-Promoted Highly Selective Carbon–Carbon Double Bond Formation of Ketones with Allyl Halides in the Presence of Diethyl Phosphite - Xie, Dengbing; Wang, Yiqiong; Yang, Bo; Zhang, Songlin (Synthesis, 2020)
The carbon–carbon double bond formation via neodymium-mediated Barbier-type reaction of ketones and allyl halides in the presence of diethyl phosphite is reported for the first time. The reaction is highly α-regioselective and was conveniently carried out under mild conditions in a one-pot fashion. From a synthetic point of view, a series of conjugated alkenes were obtained in moderate to good yields in this one-pot reaction with feasible reaction conditions.
Keywords: Barbier-type reaction; α-regioselective; one-pot reaction; diethyl phosphite